2006
DOI: 10.2310/6670.2006.00006
|View full text |Cite
|
Sign up to set email alerts
|

Regional Anesthesia: Preferred Technique for Venodilatation in the Creation of Upper Extremity Arteriovenous Fistulae

Abstract: Owing to the overall poor medical health of patients with end-stage renal disease, we have sought alternatives to the use of general anesthesia for access procedures. Furthermore, since local anesthesia (1) does not offer the motor block that is sometimes desired and (2) can be difficult to maintain when a large amount of vein needs to be transposed, we examined whether regional blocks can be useful for the creation of new arteriovenous fistulae (AVF). From August 2002 to January 2005, 41 patients scheduled fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 13 publications
3
47
0
5
Order By: Relevance
“…11 USG brachial plexus block allows more accurate placement of the injection needle, which can allow more rapid onset and longer duration of the block as well as reducing vascular and neurologic complications and reducing the volume of local anaesthetic required to achieve a successful block. 2,18,19 We achieved 100% success rate and no complications related to the USG supraclavicular block technique, which supports the notion that USG injection is a simple and safe technique in performing supraclavicular brachial plexus block. Lehtipalo and colleagues reported that interscalene brachial plexus block reduces regional sympathetic nervous activity, resulting in increases in skin blood flow, skin temperature and attenuated vasoconstrictor responses.…”
supporting
confidence: 72%
“…11 USG brachial plexus block allows more accurate placement of the injection needle, which can allow more rapid onset and longer duration of the block as well as reducing vascular and neurologic complications and reducing the volume of local anaesthetic required to achieve a successful block. 2,18,19 We achieved 100% success rate and no complications related to the USG supraclavicular block technique, which supports the notion that USG injection is a simple and safe technique in performing supraclavicular brachial plexus block. Lehtipalo and colleagues reported that interscalene brachial plexus block reduces regional sympathetic nervous activity, resulting in increases in skin blood flow, skin temperature and attenuated vasoconstrictor responses.…”
supporting
confidence: 72%
“…Some authors have advocated the use of regional anaesthesia (blocks) that could result in vasodilatation of the vessels. 25 However, the use of this technique (blocks) was not superior at the endpoint of maturation and furthermore the reliance on artificially dilated vessels could be avoided with judicious pre-operative duplex measurement of them. 25 Finally, the next step would be an investigation into the relationship between vessel diameters (cephalic vein and radial artery) and patency (primary, assisted primary and secondary) and long-term survival.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review article documented the use of NIRS for monitoring perfusion in cerebral and somatic tissue beds in a variety of settings [1]. Peripheral nerve blockade has been shown to cause vasodilatation [2,3], and may also indirectly prevent peripheral vasoconstriction from increased adrenergic activity because of surgical stress. It is assumed that these effects result in increased regional tissue perfusion, although few objective measures are readily available to document these findings.…”
Section: To the Editormentioning
confidence: 99%